The pioneer factor activity of c-Myb involves recruitment of p300 and induction of histone acetylation followed by acetylation-induced chromatin dissociation - Bettina M. Fuglerud; Marit Ledsaak; Marie Rogne; Ragnhild Eskeland; Odd S. Gabrielsen (Epigenetics & Chromatin, 2018)
Abstract Background The concept of pioneer transcription factors is emerging as an essential part of the epigenetic regulation, taking place during cell development and differentiation. However, the precise molecular mechanism underlying pioneer factor activity remains poorly understood. We recently reported that the transcription factor c-Myb acts as a pioneer factor in haematopoiesis, and a point mutation in its DNA binding domain, D152V, is able to abrogate this function. Results Here, we show that specific histone modifications, including H3K27ac, prevent binding of c-Myb to histone tails, representing a novel effect of histone modifications, namely restricting binding of a pioneer factor to chromatin. Furthermore, we have taken advantage of the pioneer-defect D152V mutant to investigate mechanisms of c-Myb’s pioneer factor activity. We show that c-Myb-dependent transcriptional activation of a gene in inaccessible chromatin relies on c-Myb binding to histones, as well as on c-Myb interacting with the histone acetyltransferase p300. ChIP assays show that both wild type and the D152V mutant of c-Myb bind to a selected target gene at its promoter and enhancer, but only wild-type c-Myb causes opening and activation of the locus. Enhancement of histone acetylation restores activation of the same gene in the absence of c-Myb, suggesting that facilitating histone acetylation is a crucial part of the pioneer factor function of c-Myb. Conclusions We suggest a pioneer factor model in which c-Myb binds to regions of closed chromatin and then recruits histone acetyltransferases. By binding to histones, c-Myb facilitates histone acetylation, acting as a cofactor for p300 at c-Myb bound sites. The resulting H3K27ac leads to chromatin opening and detachment of c-Myb from the acetylated chromatin. We propose that the latter phenomenon, acetylation-induced chromatin dissociation, represents a mechanism for controlling the dynamics of pioneer factor binding to chromatin.